(untitled) (Contemporary Mathematics, 2024)
This study explores the impact of the movement of PhD graduates and postdoctoral research fellows between academia and industry on unemployment within the academic and industry sectors. To achieve this, an optimal control model is analyzed which was developed for the population of the university, PhDs holders, postdocs, and industry compartments. The study discovered that, by offering incentives to PhD graduates and postdocs who choose to stay in academia rather than transition to industry, unemployment in the university sector can be reduced. Based on the findings, the authors advise for the governments to concentrate on offering these incentives to PhD holders and postdocs to persuade them to stay in academia. Policymakers can lower unemployment rates in both the academic and industrial sectors by putting in place measures that promote the retention of PhD holders and postdocs in academics and control their migration to the industry.